2017
DOI: 10.21307/jofnem-2017-046
|View full text |Cite
|
Sign up to set email alerts
|

Description of Aphelenchoides macrospica n. sp. (Nematoda: Aphelenchoididae) from Northwestern Iran

Abstract: Aphelenchoides macrospica n. sp. is described and illustrated from the West Azerbayjan province, northwestern Iran. The new species is characterized by its body length of 807 to 963 mm (males) and 792 to 1,094 mm (females), offset cephalic region, lateral fields with four incisures, long stylet with 15 to 16 mm length, and excretory pore situated opposite or behind the nerve ring. Pharyngeal glands overlapping intestine dorsally and extending for 90 to 121 mm, tail terminus mucronate in both sexes. Vagina dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Besides , A. persicus sp. n. along with A. varicaudatus Ibrahim and Hooper, 1994; A. xui , A. fragariae (Ritzema Bos, 1890) Christie, 1932; A. macrospica Golhasan, Heydari, Esmaeili, and Miraeiz, 2017; A. eldaricus Esmaeili, Heydari, Golhasan, and Kanzaki 2017; A. paraxui, and A. iranicus Golhasan, Heydari, Álvarez-Ortega, Esmaeili, Castillo, and Palomares-Rius, 2016; and several unidentified Aphelenchoides formed a clade with a 0.79 posterior probability support values.…”
Section: Resultsmentioning
confidence: 99%
“…Besides , A. persicus sp. n. along with A. varicaudatus Ibrahim and Hooper, 1994; A. xui , A. fragariae (Ritzema Bos, 1890) Christie, 1932; A. macrospica Golhasan, Heydari, Esmaeili, and Miraeiz, 2017; A. eldaricus Esmaeili, Heydari, Golhasan, and Kanzaki 2017; A. paraxui, and A. iranicus Golhasan, Heydari, Álvarez-Ortega, Esmaeili, Castillo, and Palomares-Rius, 2016; and several unidentified Aphelenchoides formed a clade with a 0.79 posterior probability support values.…”
Section: Resultsmentioning
confidence: 99%
“…Aphelenchoides prairiensis n. sp. grouped independently with A. macrospica Golhasan, Heydari, Esmaeili, and Miraeiz [ 59 ]. The sequence identity between A. prairiensis n. sp.…”
Section: Resultsmentioning
confidence: 99%
“…Absolutely, any change in the environment is more likely to be damaging the ecosystem. (Bastian, 1865), Aphelenchus isomerus Anderson andHooper, 1980 (Ebsary, 1991) and four species of Aphelenchoides comprising Aphelenchoies bicaudatus (Imamura, 1931) Filipjev and Schuurmans Stekhoven, 1941, Aphelenchoides richardsoni (Grewal et al, 1992), Aphelenchoides unisexus (Jain and Singh, 1984) and Aphelenchoides macrospica (Golhasan et al, 2017) were identified. It is pertinent to mention herewith that the genus Seinura could not ascertained from district Lakki Marwat.…”
Section: Resultsmentioning
confidence: 99%